Sosialisasi dan Implementasi Pembuatan Mesin Spinner pada UMKM Keripik Menjes Kyu di Kelurahan Pakunden Blitar - Gideon Setyo Budi Witjaksono; Michelle Lius; Alfinatul Fauziah; Linda Octavia Kusumawardhani; Terrano Windrianto Darmawan; Moh Sofyan Farishi (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Many of the indonesians like to eat chips as everyday snacks, one of them is menjes chips. Menjes chips are beans made from bean curd. One of the SMEs that produces the menjes chips, namely Menjes Kyu that owned by Mrs. Chalimah. In the drying process, the cips are still done conventionally, namely by simply airing them out. This can affect the quality and flavor of chips because of the amount of oil it contains. The purpose of this activity was to add to the knowledge and skill involved in the use of oil stonework (spinner), which was useful in raising the quality and value of chips. The methods used are location surveys and the filling of questionnaires, toolmaking, and socializing of automatic oil slicers. The presence of an automatic oil slicer helps to enhance the quality, flavor, and storage power of processed chips.